Indonesia Obligation to Repatriate Nationals Who Had Joined the Islamic State of Iraq and Syria - Hanif Nur Widhiyanti; Mukhlisa Ilman Nafiah Medianto (Universitas Lampung, 2022)
According to the Montevideo Convention of 1993, the requirements for founding a state are fulfilled possession of people, a region, government, capability to relate to other states, and recognition of sovereignty from other states, making it still debatable whether ISIS can be considered a state or a belligerent organization. Islamic State of Iraq and Syria claim that they possess people, a region, and a government, but in reality, they cannot make diplomatic relations with other states. The National Counter-Terrorism Agency (BNPT) has declared ISIS a radical and terrorist movement. Based on BNPT and Detachment 88 data, it is suspected that 1,276 Indonesian nationals have joined ISIS, and only approximately 297 Indonesian nationals possess Indonesian passports. A debate arises regarding whether the state of Indonesia becomes responsible for its presence and whether they still possess the status of Indonesian nationals. This article is written as the results of normative juridical research that analyzes how the state is responsible for repatriating Indonesian nationals who have joined ISIS. The research found that the nationals who joined ISIS may be categorized as Foreign Terrorist Fighters. Nonetheless, international law does not regulate the nationality status of an individual when the individual becomes a part of FTF. In principle, each state can determine the regulations that organize the acquisition and deprivation of a person's nationality; in other words, the nationality status of FTF who joined ISIS entirely depends on the national law of each state. Therefore, the government of Indonesia still possesses responsibility for returning (repatriating) WNI who have joined ISIS.